Review on production of liquid fuel from co-pyrolysis of biomass with scrap/waste tire - S.A. Babajo; J.S. Enaburekhan; I.A. Rufai (Journal of Applied Sciences and Environmental Management, 2019)
The oil produced by the pyrolysis of biomass has potential for use as a substitute for fossil fuels. However, the oil needs to be upgraded since it contains high levels of oxygen, which causes low calorific value, corrosion problems, and instability. Generally, upgrading the pyrolysis oil involves the addition of a catalyst, solvent and large amount hydrogen, which can cost more than the oil itself. In this regard, the co-pyrolysis technique offers simplicity and effectiveness in order to produce a high-grade pyrolysis oil. Co-pyrolysis is a process which involves two or more materials as feedstock. The feedstocks were biomass and tire waste. The pyrolysis of scrap tires at a temperature of 500oC produced an oil yield of 44.1 wt%. The increase in oil yield from co-pyrolysis processes of Pine wood and tire wastes was found to be 64.8 wt%. The HHV of tire waste pyrolysis liquid alone was 43.8MJ/kg while for the co-pyrolysis of tire waste and pinewoods was 46.8MJ/Kg. The results of many studies showed that the use of co-pyrolysis technique can improve the characteristics of pyrolysis oil, e.g., increase the oil yield, reduce the oxygen content, reduce the water content, and increase the calorific value of the oil.